Faculty Perception of Openness and Attitude to Open Sharing at the Indian National Open University - Panda, Santosh; Santosh, Sujata (International Review of Research in Open and Distributed Learning, 2017)
In the past decade, the educational scenario world over has significantly been impacted by open access and open education movements. The philosophy of openness and sharing forms the cornerstone of the open education movement. The distance education approaches, together with open educational resources (OER) and massive open online courses (MOOCs), are being used to serve the increasing educational needs of diverse communities. However, adoption of openness as a core value and as part of the institutional strategy still remains a challenge for academic institutions in general, and distance education institutions in particular, in developing countries like India. In this research study, the authors report an analysis of the perception of the faculty of the Indira Gandhi National Open University of India (IGNOU) about openness and their attitude towards sharing of resources in academic institutions. Data was collected through a structured questionnaire administered to the teachers and academics of IGNOU (N=69). The results indicated that: the faculty members valued sharing of resources in academic institutions; learning resources should be made available free of cost; there is a strong need for training on intellectual property rights, copyright, and creation and use of OER; and there should be an institutional policy on OER for its effective use.